A Review The use of Cerebrolysin in Pediatric Charcot Marie Tooth Disease - Jalal Al Mosawi Aamir (Journal of Neurological Research And Therapy, 2020)
Charcot Marie Tooth disease is a is a very chronic progressive hereditarymotor and sensory neuropathy characterized by progressive weakness andloss of touch sensation across various parts of the body. There are no curative or effective medical therapies that can ameliorate the disability associated with Charcot Marie Tooth disease. The aim of this paper is to describe the safe novel use of cerebrolysin in an Iraqi patient with Charcot Marie Tooth disease. Patients and Methods A boy who was born on the seventh of November, 2009, and was first seen on 29th of January, 2018 at the Children Teaching Hospital of Baghdad Medical City and had Charcot Marie Tooth disease was observed. He had difficulty in walking and abnormal gait that made him left first grade primary school. The nerve conduction study and electromyography study supported the clinical diagnosis of chronic symmetric sensori-motor polyneuropathy of moderated severity. The boy was treated with a safe novel therapy for one month. He receivedten doses of 3 ml intra-muscular cerebrolysin every three days. Results The short term effect of the therapy was dramatic with noticeable improvement that has never been reported before with this condition. Conclusion Further studies enrolling more patients are highly recommended.
Keywords: Charcot-Marie-Tooth disease